CD14highCD16+ monocytes are the main producers of Interleukin-10 following clinical heart transplantation - Ludwig, Kristina; Chichelnitskiy, Evgeny; Kühne, Jenny F.; Wiegmann, Bettina; Iske, Jasper; Ledwoch, Nadine; Ius, Fabio; Beushausen, Kerstin; Keil, Jana; Iordanidis, Susanne; Rojas, Sebastian V.; Salman, Jawad; et al. (Frontiers in immunology, 2023)
Introduction: Following heart transplantation, a cascade of immunological responses is initiated influencing the clinical outcome and long-term survival of the transplanted patients. The anti-inflammatory cytokine interleukin-10 (IL-10) was shown to be elevated in the blood of heart transplant recipients directly after transplantation but the releasing cell populations and the composition of lymphocyte subsets following transplantation have not been thoroughly studied. Methods: We identified immune cells by immunophenotyping and analyzed intracellular IL-10 production in peripheral blood mononuclear cells (PBMC) of heart transplanted patients (n= 17) before, directly after and 24h post heart transplantation. The cells were stimulated with lipopolysaccharide or PMA/Ionomycin to enhance cytokine production within leukocytes in vitro. Results and discussion: We demonstrate that intermediate monocytes (CD14high CD16+), but not CD8+ T cells, CD4+ T cells, CD56+ NK cells or CD20+ B cells appeared to be the major IL-10 producers within patients PBMC following heart transplantation. Consequently, the absolute monocyte count and the ratio of intermediate monocytes to classical monocytes (CD14+CD16-) were specifically increased in comparison to pre transplant levels. Hence, this population of monocytes, which has not been in the focus of heart transplantation so far, may be an important modulator of clinical outcome and long-term survival of heart transplant recipients. Alteration of blood-circulating monocytes towards a CD14high CD16+ phenotype could therefore shift the pro-inflammatory immune response towards induction of graft tolerance, and may pave the way for the optimization of immunosuppression.